Yıkıcı Liderliğin Örgütsel Sapmaya Etkisinde Örgütsel Sinizmin Rolü: Konya İli Gıda Sektöründe Bir Uygulama - Erdem, Ahmet Tuncay (Muş Alparslan Üniversitesi, 2021)
Destructive leadership behaviors cause insecurity in the relationships between employees and managers in business life and can lead to various organizational problems. This study's main purpose is to determine whether "organizational cynicism" functions as a mediator in the effect of destructive leadership behaviors on organizational deviation. The research is designed according to the quantitative research method. Research data were collected from an enterprise operating in the Konya food production sector (n = 283) using the full count sampling technique. Descriptive analysis, difference, and relationship tests were carried out in the research. According to the findings obtained from the research data analysis, the positive effects of destructive leadership behavior on organizational deviation and organizational cynicism were determined. It has been determined that organizational cynicism has a mediating role in the effect of destructive leadership on the organizational deviation. As a result, destructive leadership behavior triggers negative behaviors towards employees in the organization as a negative behavior. It can be seen that the perceptions of organizational deviation and cynicism increase in the employees as the negativity come from the manager.

Yıkıcı liderlik davranışları, iş yaşamında çalışanlarla yöneticilerin ilişkilerinde güvensizliğe neden olmakta, örgütte çeşitli sorunlara yol açabilmektedir. Bu araştırmanın temel amacı, yıkıcı liderlik davranışlarının örgütsel sapmaya etkisinde “örgütsel sinizm”in aracı işlev görüp görmediğini belirlemektir. Araştırma nicel araştırma yöntemine göre tasarlanmıştır. Araştırma verileri, Konya gıda üretim sektöründe faaliyet gösteren bir işletmeden (n=283) tam sayım örnekleme tekniğine göre toplanmıştır. Araştırmada betimsel analizler, fark ve ilişki testleri yapılmıştır. Araştırma verilerinin analizinde elde edilen bulgulara göre yıkıcı liderlik davranışının, örgütsel sapma ve örgütsel sinizme pozitif etkileri belirlenmiştir. Yıkıcı liderliğin örgütsel sapmaya etkisinde örgütsel sinizmin aracı rolü olduğu belirlenmiştir. Sonuç olarak yıkıcı liderlik davranışı olumsuz bir davranış olarak örgütte çalışanlara yönelik olumsuz davranışları tetiklemektedir. Olumsuzluğun yöneticiden gelmesiyle de çalışanlarda örgütsel sapma ve sinizm algılarının artması görülebilir.
The Role of Organizational Cynicism in the Effect of Destructive Leadership on Organizational Deviation: a Food Sector Research in Konya
anemon
Keywords: Destructive Leadership; Organizational Deviance; Organizational Cynicism; Yıkıcı Liderlik; Örgütsel Sapma; Örgütsel Sinizm